Imanensi Kiai Ta’lim dalam Perspektif Filsafat Sosial Emile Durkheim di Pondok Pesantren Syifaul Mu’minin Ciomas - Latip Ridwan; Sholahuddin Al Ayubi; Masykur Wahid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A kiai (Islamic scholars) is an instrumental figure for Muslims, especially their students. Kiai are expected to behave well according to Islamic law. However, many kiai fall into sin. Lack of vigilance in maintaining their faith can lead them to indulge in worldly pleasures and commit reprehensible acts. Therefore, this study focuses on the kiai's identity as a symbol inherent in Islam. The various behaviors carried out during the kiai's da'wah journey will influence the formation of an Islamic religious identity, encompassing its teachings. Therefore, this research was conducted with the aim of presenting the concept of the Immanence of Kiai Ta'lim, the forming and destroying factors, and the influence of the immanence of Kiai Ta'lim on the social environment. In this study, the researcher used a qualitative research method (Field research) to obtain maximum data results. The author used data processing techniques to obtain data in this study by conducting observations at the Syifa'ul Mu'minin Islamic Boarding School, interviews with the leaders of the Kiai of the Syifa'ul Mu'minin Islamic Boarding School, and documentation. The results of this study indicate that the Immanence of Kiai Ta'lim has a very large influence on individuals and the social environment. The Immanence of Kiai Ta'lim is spiritual wisdom by realizing the presence of God (Allah) who is one with one's soul or heart, both in educational missions and in social missions.